Super absorbent resin water-retaining agent, preparation method thereof and plant straw-based dust suppressant

By preparing high-absorbent resin water retention agent, dust suppressors are prepared using plant straw as raw materials, which solves the problems of dust pollution and low solid waste reuse rate on construction sites, and achieves the effect of effectively suppressing dust and improving solid waste utilization rate.

CN119306902APending Publication Date: 2025-01-14XIHUA UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411430153.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Environmental pollution problems at dust sites such as construction sites are serious. The existing technology is not effective enough to treat dusty open pollution sources, and the solid waste reuse rate is low, which affects environmental and resource consumption.

Method used

Using highly absorbent resin water retention agent and its preparation method, using agricultural and forestry plant straw as raw material to prepare plant straw-based dust inhibitor, carboxymethyl straw cellulose powder is prepared by aqueous solution polymerization, and mixed solution with acrylic acid-sodium hydroxide and initiator Combining components such as crosslinking agents to form a highly absorbent resin water retention agent, which is used to prepare plant straw-based dust inhibitors.

Benefits of technology

Effectively suppress the evaporation of moisture in dust, form a dense consolidation layer, reduce dust, and dust inhibitors do not contain harmful substances, are easy to transport and store, have strong adhesion and water retention properties, are suitable for spraying and dust suppression, and improves the comprehensive solid waste Utilize and circular economy benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306902A_ABST
    Figure CN119306902A_ABST
Patent Text Reader

Abstract

The invention relates to a super absorbent resin water-retaining agent and a preparation method thereof and a plant straw-based dust suppressant, the super absorbent resin water-retaining agent is prepared by the following steps: preparing carboxymethyl straw cellulose powder by using plant straw as a raw material, and then preparing the super absorbent resin water-retaining agent by using the carboxymethyl straw cellulose powder as a raw material through an aqueous solution polymerization method; the dust suppressant provided by the invention has the beneficial effects that after the dust suppressant provided by the invention is sprayed on the surface of dust, the dust can be agglomerated together, the evaporation of moisture in raised dust is reduced, and the raised dust is effectively inhibited; and the dust suppressant does not contain substances harmful or irritant to human bodies, all components in a formula system of the dust suppressant can be mutually fused at normal temperature, and the dust suppressant is suitable for being sprayed for dust suppression and is easy to transport and store.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water retaining agents and dust suppressants, and in particular to a highly water-absorbent resin water retaining agent and a preparation method thereof, and a plant straw-based dust suppressant. Background Art

[0002] With the continuous development of society, the number of construction sites and other sites that cause dust is increasing day by day, and the scale is also expanding. Dust is mainly generated by human activities such as urban construction, crop burning and vehicle exhaust emissions. Corresponding environmental pollution problems have followed one after another, seriously affecting the treatment effect of patients and even endangering their lives and health.

[0003] Crop straw refers to the plant residues such as stems, stalks, leaves, flowers, and fruits of crops in agricultural production, including grain straw, oil straw, cotton fiber straw, fruit tree straw, vegetable straw, etc. After being cut, baled, stacked, loaded, and transported, the straw becomes crop straw waste. Crop straw is a tangible waste generated during the production process, so it can be classified as solid waste. In particular, in my country, the recycling rate of solid waste represented by agricultural and forestry plant straw is low, and most of it is still incinerated, which has a great impact on the environment.

[0004] Based on this, a super absorbent resin water retaining agent and a preparation method thereof and a plant straw-based dust suppressant are proposed. The dust suppressant is prepared with agricultural and forestry plant straw as raw material, which can solve the open pollution source caused by dust, and is conducive to the development of a circular economy, strengthening the comprehensive utilization of solid waste, reducing resource consumption, saving energy and reducing carbon emissions. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a super absorbent resin water retaining agent and a preparation method thereof, and a plant straw-based dust suppressant. The dust suppressant is prepared using agricultural and forestry plant straw as raw materials, which can solve the open pollution source caused by flying dust, and is conducive to the development of a circular economy, strengthening the comprehensive utilization of solid waste, reducing resource consumption, and saving energy and reducing carbon emissions.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The present invention discloses a highly absorbent resin water-retaining agent, which is prepared by first using plant straw as a raw material to prepare carboxymethyl straw cellulose powder, and then using the carboxymethyl straw cellulose powder as a raw material through an aqueous solution polymerization method.

[0008] A method for preparing the above-mentioned super absorbent resin water-retaining agent comprises the following steps:

[0009] S1. Wash, dry, cut and then crush and sieve the straw to obtain a plant straw powder sample;

[0010] S2, mixing the plant straw powder sample with deionized water to obtain a mixed solution;

[0011] S3, adding alkaline solution to the mixed solution, reacting in a water bath at 30-40°C, then heating to 70-80°C and adding sodium chloroacetate to react for 1-2 hours;

[0012] S4, filtering, washing and drying the solution obtained by the reaction in step S3 to obtain carboxymethyl straw cellulose powder;

[0013] S5. Add carboxymethyl straw cellulose powder, acrylic acid-sodium hydroxide mixed solution, initiator, crosslinking agent and deionized water in a three-necked flask in sequence, filter three times with nitrogen, stir and react in a water bath at 65-75°C to form a gel, then heat to 90-98°C and keep warm for 0.5-1h;

[0014] S6, drying, crushing and sieving the gel obtained in step S5 to obtain a super absorbent polymer water retaining agent sample (plant straw-based super absorbent polymer water retaining agent).

[0015] Further, in S2, 20 to 30 g of the plant straw powder sample is mixed with 200 to 300 ml of deionized water to obtain a mixed solution;

[0016] In S3, 35-45 ml of 20% sodium hydroxide by mass is added to the mixed solution, reacted in a water bath at 30-40° C., then the temperature is raised to 70-80° C. and 15-40 g of sodium chloroacetate is added to react for 1-2 hours;

[0017] In S5, 10-20 g of carboxymethyl straw cellulose powder, 70-80 ml of acrylic acid-sodium hydroxide mixed solution, 1.5-2 g of initiator, 0.5-0.7 g of cross-linking agent and 100-150 ml of deionized water are added in sequence to a three-necked flask. After nitrogen is passed through and filtered three times, the mixture is placed in a 65-75° C. water bath and stirred to allow a polymerization reaction to occur. The temperature in the flask rises rapidly to form a gel, which is then raised to 90-98° C. and kept warm for 0.5-1 h.

[0018] Further preferably, in S2, 30 g of the plant straw powder sample is mixed with 300 ml of deionized water to obtain a mixed solution;

[0019] In S3, 40 ml of 20% sodium hydroxide was added to the mixed solution, and the mixture was reacted in a 35°C water bath for 1 hour, and then the temperature was raised to 75°C and 30 g of sodium chloroacetate was added to react for 1.5 hours;

[0020] In S5, 15 g of carboxymethyl straw cellulose powder, 75 ml of acrylic acid-sodium hydroxide mixed solution, 1.8 g of initiator, 0.6 g of cross-linking agent and 127.5 ml of deionized water are added to a three-necked flask in sequence, and the mixture is filtered through nitrogen for three times (1-2 min each time) and then placed in a 70°C water bath with stirring to allow a polymerization reaction to occur. The temperature in the flask rises rapidly and a gel is formed, which is then raised to 95°C and kept warm for 0.5-1 h.

[0021] Furthermore, the preparation method of the acrylic acid-sodium hydroxide mixed solution is:

[0022] A 20% sodium hydroxide solution is mixed with acrylic acid to prepare a mixed solution of acrylic acid and sodium hydroxide with a neutralization degree of 60%.

[0023] Furthermore, the straw includes but is not limited to one or more of wheat straw, turkey straw, chili straw, bean straw, rice straw, eggplant straw, corn straw, licorice straw, and bamboo poles.

[0024] Furthermore, in step S5, the initiator is potassium persulfate; and / or the cross-linking agent is N,N'-methylenebisacrylamide.

[0025] The present disclosure also provides a plant straw-based dust suppressant, which is prepared from the following components:

[0026] 0.1% to 0.3% binder, 1% to 4% water retaining agent, 0.1% to 0.8% surfactant, and the balance is deionized water;

[0027] Wherein, the water retaining agent is the above-mentioned super absorbent resin water retaining agent or the super absorbent resin water retaining agent prepared by the above-mentioned preparation method.

[0028] Furthermore, the pH value of the plant straw-based dust suppressant is 6.5-7.

[0029] Furthermore, the surfactant is octyl glucoside.

[0030] Furthermore, the binder is hydroxyethyl cellulose, and the viscosity of the hydroxyethyl cellulose is 100,000.

[0031] Beneficial effects of the present invention:

[0032] (1) The present disclosure provides a super absorbent resin water retainer and a preparation method thereof and a plant straw-based dust suppressant. The plant straw-based dust suppressant is composed of super absorbent resin water retainer, hydroxyethyl cellulose, cinnamyl glucoside and other components; the plant straw water retainer has water retention and water absorption functions, the hydroxyethyl cellulose has a bonding effect, and the cinnamyl glucoside has a wetting effect; after spraying the plant straw dust suppressant on the dust, the dust can be agglomerated together to form a dense consolidation layer, which further reduces the evaporation of water in the dust, reduces the evaporation of water, and effectively suppresses the dust; and the plant straw dust suppressant does not contain any substance that is harmful or irritating to the human body, and the components in the plant straw-based dust suppressant formula system can be mutually integrated at room temperature, are easy to transport and store, and are suitable for spraying to suppress dust;

[0033] (2) In the plant straw-based dust suppressant, both the water retainer and the binder have a significant effect on the bonding performance, among which the binder has the greatest influence, and the combination of the two has a strong bonding property, that is, in this scheme, the water retainer and the binder play a synergistic role;

[0034] In addition, the viscosity of the dust suppressant cannot be too large, otherwise it will be difficult to spray. Therefore, this solution is to add a small amount of binder as an auxiliary material of the dust suppressant to make the solution not too viscous. Thanks to the synergistic effect of the water retaining agent and the binder, the final plant straw-based dust suppressant product not only has the water absorption performance of the water retaining agent, which is convenient for spraying, but also has a much improved bonding performance of the dust suppressant solution.

[0035] (3) In the early preparation process of the super absorbent resin water retaining agent, the amount of NaOH used in this scheme is small, and the sodium chloroacetate used has low toxicity, which is beneficial to the environmental safety and application of the product;

[0036] In addition, in this scheme, 15g of straw powder can be used to obtain about 20g of carboxymethyl straw cellulose, and finally about 25g of super absorbent resin water retaining agent particles can be obtained through polymerization reaction. Therefore, this scheme has high mass conversion efficiency and good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a diagram showing the state of the film formed after spraying the plant straw-based dust suppressant;

[0038] Figure 2 This is a comparison chart of water retention rates of various water-retaining agents with a mass concentration of 1.5% after evaporation for 7 hours;

[0039] Figure 3 This is a comparison chart of water retention rates of various water-retaining agents with a mass concentration of 2.0% after evaporation for 7 hours;

[0040] Figure 4 This is a comparison chart of water retention rates of various water-retaining agents with a mass concentration of 2.5% after evaporation for 7 hours;

[0041] Figure 5 This is a comparison chart of the anti-evaporation rate of different types of water-retaining agents at a concentration of 2% after 7 hours;

[0042] Figure 6 It is a schematic diagram of the viscosity values ​​of three binders at different mass concentrations at room temperature (20°C);

[0043] Figure 7 is the surface tension curve of the surfactant;

[0044] Figure 8 3D surface plot and contour plot of the interaction effect between SAP and HEC (10S) on viscosity;

[0045] Fig. 9 3D surface plot and contour plot of the interaction effect of SAP and APG0810 on viscosity;

[0046] Fig.10 3D surface map and contour map of the interaction effect of HEC (10S) and APG0810 on viscosity;

[0047] Fig.11 3D surface and contour plots of the interaction effect between SAP and HEC (10S) against the evaporation rate;

[0048] Fig.12 3D surface and contour plots for the interaction effect between SAP and APG0810 against the evaporation rate;

[0049] Fig.13 3D surface and contour plots of the interaction effect between HEC(10S) and APG0810 against the evaporation rate;

[0050] Fig.14 3D surface and contour plots of the interaction between SAP and HEC (10S) on surface tension;

[0051] Fig.15 3D surface plot and contour plot of the interaction effect between SAP and APG0810 on surface tension;

[0052] Fig.16 3D diagram and contour map of the interaction effect between HEC (10S) and APG0810 on surface tension;

[0053] Fig.17 It is a comparison chart between the actual value and the value predicted by the equation;

[0054] Fig.18 Schematic diagram of the morphology of soil samples after being immersed in five solutions;

[0055] Fig.19Schematic diagram of soil pH value at the collection point;

[0056] Fig. 20 The dust samples are shown at 0min, 1min and 10min after spraying the straw-utilizing dust suppressant solution;

[0057] Fig.21 The dust samples are shown 0min, 1min, and 10min after spraying water;

[0058] Fig. 22 This is a schematic diagram after spraying straw-utilizing dust suppressant;

[0059] Fig.23 This is a schematic diagram after spraying water;

[0060] Fig.24 This is the particle morphology of the marginal soil 3 hours after spraying the straw-utilizing dust suppressant (H2);

[0061] Fig.25 This is the particle morphology of the edge soil 3 hours after spraying water;

[0062] Fig.26 Soil wetting diagram for spraying H1, H2, H3, H4, and H5;

[0063] Fig. 27 This is a graph showing the growth of five pots of Chinese cabbage seedlings 96 hours after planting;

[0064] Fig.28 This is the growth trend chart of cabbage seedlings for 144 hours;

[0065] Fig.29 This is a comparison chart of the soil sample H2 before and after erosion (the spraying volume is 1.0L / ㎡);

[0066] Fig.30 This is a comparison chart of the H2 soil sample before and after erosion (the spraying volume is 1.5L / ㎡);

[0067] Fig.31 This is a comparison chart of the soil sample H2 before and after erosion (the spraying volume is 2.0L / ㎡);

[0068] Fig.32 This is a comparison chart of the soil sample H2 before and after erosion (the spraying volume is 2.5L / ㎡);

[0069] Fig.33 This is a comparison chart of the mass loss rate of soil samples under different spraying amounts of H2;

[0070] Fig.34 The spraying volume is 2L / m 2 Comparison of mass loss rates of soil samples sprayed with different dust suppressants under different conditions. DETAILED DESCRIPTION

[0071] The embodiments of the present invention are described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used without the manufacturer's indication are all conventional products that can be obtained commercially.

[0072] Example 1

[0073] In this example, 9 kinds of agricultural and forestry waste straws were used as raw materials to study the formation of highly absorbent resin water retainers by free radical graft copolymerization of acrylic acid monomers. The water retention performance of each straw-based resin water retainer with different mass concentrations was investigated and compared with 3 common water retainers on the market (water retainer 1#, water retainer 2#, water retainer 3#) and a pure water control group.

[0074] Nine kinds of agricultural and forestry waste plant straws (wheat straw, turkey straw, chili straw, bean straw, rice straw, eggplant straw, corn straw, licorice straw, bamboo pole) were used as raw materials to prepare super absorbent resin water retaining agents. Preparation method:

[0075] The plant straw was washed and dried in an oven, and then cut into small segments of 5 to 10 cm, crushed by a grinder, and passed through a 100-mesh standard sieve to obtain a plant straw powder sample.

[0076] In a three-necked flask, 30 g of straw powder was mixed with 300 ml of deionized water to obtain a mixed solution. 40 ml of 20% sodium hydroxide was added to the mixed solution, and the mixture was reacted in a 35°C water bath for 1 hour, and then the temperature was raised to 75°C and 30 g of sodium chloroacetate was added to react for 1.5 hours. After filtration, washing and drying, carboxymethyl straw cellulose powder was obtained.

[0077] A 20% sodium hydroxide solution was mixed with acrylic acid to prepare a mixed solution of acrylic acid and sodium hydroxide (acrylic acid-sodium hydroxide mixed solution) with a neutralization degree of 60%.

[0078] In a three-necked flask, 15g of carboxymethyl straw cellulose powder, 75ml of acrylic acid-sodium hydroxide mixed solution, 1.8g of initiator potassium persulfate, 0.6g of cross-linking agent N,N'-methylenebisacrylamide, and 127.5ml of deionized water were added in sequence, and after nitrogen filtration, the mixture was placed in a 70°C water bath and stirred to form a gel, and the temperature was raised to 95°C and kept warm for 1h. The gel was taken out, dried, crushed, and sieved to finally obtain a sample of a highly absorbent resin water retainer.

[0079] Effect verification:

[0080] The 9 water retaining agent samples prepared in Example 1, as well as commercially available water retaining agent 1#, water retaining agent 2#, and water retaining agent 3# were used as research objects, and water retaining agent solutions with concentrations of 1.5%, 2%, and 2.5% were prepared respectively.

[0081] Place an equal amount of dried and sieved dust in an aluminum box, and weigh each aluminum box as W1. Spray the above water retaining agent solutions of different types and concentrations on the dust surface at a spraying volume of 15 ml. At the same time, take the dust sample sprayed with pure water as the control group, weigh it as W2. Immediately put the aluminum box sprayed with water retaining agent into a 75℃ oven for evaporation. The weight after evaporation is recorded as W3.

[0082] E=(W3-W1) / (W2-W1)……(1)

[0083] Where: E is the water retention rate;

[0084] W1 is the weight of dust and aluminum box (g);

[0085] W2 is the weight after spraying water retaining agent (g);

[0086] W3 is the weight (g) after i hours.

[0087] The experimental results are as follows Figure 2-4 As shown: A1-A9 are water-retaining agents prepared from wheat, turmeric, chili pepper, bean, straw, eggplant, corn, licorice, and bamboo straw respectively; B1-B3 are water-retaining agents ethylene glycol, propylene glycol, and triethanolamine purchased on the market respectively; C1 is water.

[0088] from Figure 2-4 It can be seen that the water retention rate of wheat straw-based super absorbent resin water retainer (A1) at 1.5%, 2%, and 2.5% mass concentrations after 7 hours is 37%, 40%, and 40%, respectively, which are better than other water retainers, and the fluidity of 2% mass concentration is good, which is conducive to on-site spraying. It has great market application value. And the wheat straw-based super absorbent resin water retainer solution with a mass concentration of 2% is the water retainer with the best performance.

[0089] Example 2

[0090] Preparation of preferred plant straw-based dust suppressants:

[0091] Raw materials: 0.1% hydroxyethyl cellulose (10S), 1.82% wheat straw-based super absorbent resin water retaining agent (prepared in Example 1), 0.8% cinnamyl glucoside, and the balance is water.

[0092] The above raw materials are mixed to obtain a plant straw-based dust suppressant. The composition of each raw material is screened in the following manner:

[0093] (1) Selection of water retaining agent

[0094] The anti-evaporation rate of different types of water retaining agents at a concentration of 2% was tested. The anti-evaporation rate of different types of water retaining agents at a concentration of 2% after 7 hours is as follows: Figure 5 shown.

[0095] from Figure 5 It can be seen that the water retainer prepared from plant straw in this embodiment has significant anti-evaporation performance compared with the pure water control group. When the solution concentration is 2%, the anti-evaporation performance of the wheat water retainer is the best, reaching 40%. It should be noted that the present disclosure also tested the anti-evaporation performance of the wheat water retainer with a concentration of 2.5%, and found that when the concentration is 2% and 2.5%, the anti-evaporation performance is the same as 40%, but 2% can reduce the spraying amount to a certain extent. From the perspective of anti-evaporation performance and economy, it is more reasonable to prefer a wheat water retainer solution with a mass concentration of about 2%.

[0096] However, considering that there may be certain interactions between water retaining agents, binders and surfactants when compounding straw-utilizing dust suppressants, the range near the highest point of the anti-evaporation rate of wheat water retaining agent was selected for further optimization research, and three levels of mass concentration of 1.5%, 2% and 2.5% were selected for subsequent response surface optimization analysis.

[0097] (2) Selection of binder

[0098] Taking the adhesive performance of the adhesive as an indicator, the adhesive with excellent adhesive performance is selected as one of the raw materials of the dust suppressant. The viscosity of the three viscous materials at room temperature (20°C) changes with mass concentration as shown in the figure. Figure 6 shown.

[0099] according to Figure 6 It can be seen that the viscosity of HEC (10S) solution increases rapidly with the increase of mass concentration, and exceeds 100mpa·s at a mass concentration of 0.4%. HEC (3S) is the second, while the viscosity of SA solution changes the least. Therefore, HEC (10S), which has a higher viscosity among the three, is selected as the compounding agent of dust suppressant. Since the viscosity of the binder is too high and it is difficult to spray, three levels at low concentrations (0.1%, 0.2%, and 0.3%) are selected for response surface optimization analysis.

[0100] (3) Selection of surfactant

[0101] Taking the surface tension of surfactant as an indicator, the surfactant with excellent performance is selected as one of the raw materials of dust suppressant. The surface tension of the four surfactants measured changes with mass concentration as shown in Figure 7 shown.

[0102] from Figure 7It can be seen that the four surfactants can quickly reduce the surface tension of the solution. The APG0810 solution reached 25.2mN / m at a mass concentration of 0.6%, which is lower than the other three surfactants, so the wetting performance is better than other surfactants. Therefore, APG0810 is selected as the component of the dust suppressant. For the optimization ratio analysis, the range near the lowest value of the surface tension is selected for optimization research, that is, 0.4%, 0.6%, and 0.8% are used for response surface optimization analysis.

[0103] Preparation method of dust suppressant:

[0104] ① Experimental design was performed according to Box-Design in Design-Expert13.0. On the basis of single-factor experiments, the three factors were the binder hydroxyethyl cellulose (HEC, 10S), the wheat straw-based super absorbent resin water-retaining agent (SAP), and the surfactant cinnamyl glucoside (APG0810), and the main functions of the three reagents: viscosity (Y1), anti-evaporation rate (Y2), and surface tension (Y3) were used as three levels to conduct experimental design under three factors and three levels. The horizontal factor (Factor) refers to a variable in the experimental design, and the different levels of this variable will affect the response variable. In the response surface method, important factors are usually selected as experimental variables, and then the changes in the response variables are observed by comparing the levels of these factors. The factor coding and level settings of this experiment are shown in Table 1.

[0105] In this embodiment, the inventors conducted 17 independent tests. The response surface design schemes and experimental results of the 17 independent tests are shown in Table 2.

[0106] Table 1 Response surface analysis factors and levels

[0107]

[0108] Note: "-1 means low level, 0 means medium level, 1 means high level"

[0109] Table 2 Experimental design and response results

[0110]

[0111]

[0112] ② Establishment of regression model and variance analysis

[0113] Based on variance analysis, the test data were fitted to obtain the quadratic regression polynomial equations of viscosity (Y1), anti-evaporation rate (Y2), and surface tension (Y3), as shown in formulas (a), (b), and (c). The influence of each factor on the response value was evaluated by the equation coefficients. The credibility of the response surface model was verified by variance analysis.

[0114] Y1=2048.66-1388.09A-13525.35B-569.95C+5168.00AB+38.00AC+662.50BC+266.86A 2 +21921.50B 2 +366.63C 2 (a)

[0115] Wherein: ABC are SAP, HEC (10S), APG0810 respectively, and Y1 is the viscosity value.

[0116] From the coefficients of the regression equation, it can be seen that the order of influence of the three factors A, B, and C on the viscosity value is: C<A<B. HEC (10S) has the greatest influence on viscosity, followed by SAP, and APG0810 has the least influence on the viscosity response. The viscosity regression model F=3543.46, P<0.0001, indicating that the fitted quadratic regression model is highly significant. The lack of fit term is an important data used to evaluate the reliability of the equation. The lack of fit term F=0.5147, P=0.6939, indicating that the missing term in the model is not significant compared to the pure error, and the model is effective and reasonable. R 2 =0.9998, This indicates that the model can explain 99.98% of the viscosity value changes. The coefficient of variation CV = 1.86% < 10%, indicating that the model has less abnormal data and is effective and reasonable.

[0117] Y2=-44.9875+60.325A-72.00B+28.4375C-20.50AB-8.00AC+28.75BC-13.10A 2 -130.00B 2 -14.375C 2 (b)

[0118] From the coefficients of the regression equation, it can be seen that the order of the influence of the three factors A, B, and C on anti-evaporation is: C<B<A. The F of the anti-evaporation regression model is 84.38, P<0.0001, indicating that the fitted quadratic regression model is highly significant. The lack of fit term F=0.3533=0.3533, P=0.7904, indicating that the missing term in the model is not significant compared with the pure error, and the model is effective and reasonable. R 2 =0.9909, This indicates that the model can explain 99.09% of the viscosity value changes. The coefficient of variation CV = 1.09% < 10%, indicating that the model has less abnormal data and is effective and reasonable.

[0119] Y3=16.7375+4.95A+24.625B+5.6875C-4.50AB-0.25AC-2.50BC-1.00A 2 -37.50B 2 -4.375C 2 (c)

[0120] From the coefficients of the regression equation, we can see that the order of influence of factors A, B, and C on surface tension is: A<B<C. The F of the surface tension regression model is 41.95, P<0.0001, indicating that the fitted quadratic regression model is highly significant. The lack of fit term F=0.005, P=0.7022, indicating that the missing term in the model is not significant compared to the pure error, and the model is effective and reasonable. R 2 =9818, This indicates that the model can explain 98.18% of the viscosity value changes. The coefficient of variation CV = 0.2495% < 10%, indicating that the model has less abnormal data and is effective and reasonable.

[0121] In summary, by establishing a response surface experimental design model, the quadratic regression equations of the three response values ​​were obtained. The variance analysis results of the equations showed that the fitting effect was significant, indicating that the regression model can effectively predict the change patterns of the solution's viscosity, anti-evaporation rate, and surface tension value.

[0122] ③Two-factor interaction analysis

[0123] In order to further study the effect of the interaction between wheat straw-based super absorbent polymer (SAP), hydroxyethyl cellulose (HEC, 10S) and octyl glucoside (APG0810) on the viscosity, anti-evaporation rate and surface tension of dust suppressant solution, and then obtain the dust suppressant with the best ratio, the experimental model was established using Design-Expert software, one of the factors was fixed, the response surface graph and contour graph of the other two factors were drawn, and the effect of the interaction between the two factors was analyzed.

[0124] The response surface and contour plots can directly reflect the degree of influence of the interaction between two factors on the impact value. The steeper the response surface and the denser the contour lines, the more significant the response to the response value. The more elliptical the contour lines are, the stronger the interaction between the two factors is. The contour plot is the prototype, which indicates the opposite. Figure 7-19 shown.

[0125] from Figure 8 It can be seen that the response surface diagram of the interaction between HEC (10S) and SAP changes greatly. This is because HEC (10S) and SAP solution have adhesive properties. The fusion of the two causes the viscosity value to rise rapidly, and the interaction is very significant. Therefore, in terms of the influence of adhesive properties, wheat straw-based super absorbent polymer water retaining agent (SAP) and hydroxyethyl cellulose (HEC, 10S) have a synergistic effect. Fig. 9 It can be seen from the graph that when the mass concentration of SAP is 2%, as the mass concentration of APG0810 increases, the viscosity of the dust suppressant solution increases slowly, and the interaction is not significant. Fig.10 It can be seen that when the mass concentration of HEC (10S) is 0.2%, as the mass concentration of APG0810 increases, the viscosity value of the dust suppressant solution still does not increase significantly, indicating that APG0810 has little effect on the viscosity of the dust suppressant solution and the interaction is not significant.

[0126] from Fig.11 It can be seen that when the mass concentration of SAP is 2%, as the mass concentration of HEC (10S) increases, the anti-evaporation rate of the plant straw-based dust suppressant solution increases first and then decreases. Fig.12 It can be seen from the figure that when the mass concentration of SAP is 2%, as the mass concentration of APG0810 increases, the anti-evaporation rate of the dust suppressant solution increases first and then slowly decreases. Fig.13 It can be seen that when the mass concentration of HEC (10S) is 0.2%, as the mass concentration of APG0810 increases, the anti-evaporation rate of the dust suppressant solution shows a trend of slowly increasing and then slowly decreasing.

[0127] from Figures 11 to 13 From the 3D response surface diagram, we can see that the response surface diagram of the anti-evaporation rate of AB, AC, and BC is a parabola, and the response surface changes greatly, with the color changing from blue to red, indicating that the interaction of AB, AC, and BC is very significant. From the contour map, the contour lines of AB, AC, and BC are all elliptical, indicating that the interaction of two factors of the three factors shows a significant effect.

[0128] from Fig.14 It can be seen from the figure that the surface tension response surface of the interaction between factors A and B is a parabola, and the response surface has a large variation range. From the 2D figure, it can be seen that the contour lines are elliptical, indicating that the interaction between AB is very significant. Fig.15 , Fig.16 It can be seen that although the 3D graph of the interaction between the two factors A, C and B, C is a parabola, the contour lines in the 2D graph are circles, so the interaction is not significant.

[0129] Model verification and determination of dust suppressant ratio

[0130] The distribution diagrams of the predicted values ​​and actual values ​​of the three models are as follows: Fig.17 As shown, the dotted line in the figure is the ±5% error range of y=x.

[0131] from Fig.17 It can be seen that all the pilots are distributed around the straight line y=x, which means that the predicted values ​​and measured values ​​of the three models are not much different, indicating that the optimal ratio obtained by the model through prediction is reasonable.

[0132] According to the use requirements of dust suppressants, too high viscosity is not required. When the viscosity is about 100mpa·s, it can ensure adhesion while being conducive to the spraying of spraying equipment, saving raw materials and reducing economic burden. The maximum value is selected for the anti-evaporation rate. The higher the anti-evaporation rate, the stronger the water retention and absorption capacity of the dust suppressant, and the longer the dust suppression lasts. The minimum value is selected for the surface tension value. The smaller the surface tension value, the better the wetting effect of the dust suppressant, so as to achieve the ideal dust suppression effect.

[0133] Therefore, the dust suppressant ratio obtained through software analysis is:

[0134] 1.93% wheat straw-based super absorbent polymer water retaining agent (SAP), 0.10% hydroxyethyl cellulose (HEC, 10S), and 0.80% octyl glucoside (APG0810).

[0135] The corresponding actual test was carried out according to the dust suppressant ratio obtained by software analysis, and the verification results are shown in Table 3.

[0136] Table 3 Verification results of dust suppressant energy index

[0137] index Viscosity Y1(mpa·s) Anti-evaporation rate (%) Surface tension (mN / m) Test 1 101.5 26.4 25.0 Test 2 102.8 28.5 25.1 Test 3 103.7 27.1 25.1 Measured average value 102.7 27.3 25.1 Model prediction value 100.7 27.8 24.9

[0138] As can be seen from Table 3, the predicted values ​​obtained by the response surface model have a small relative error with the true values, and the actual viscosity is 102.27mpa·s, the anti-evaporation rate is 27.33%, and the surface tension is 25.07mN / m. It proves that the fitting of the test model is effective and reasonable, and the regression equation can effectively predict the variation law of the three response values ​​of viscosity, anti-evaporation rate, and surface tension. The ratio optimization results have certain significance in practical engineering applications.

[0139] How to use plant straw-based dust suppressant:

[0140] Use a high-pressure sprayer at the construction site, spray at a rate of 2L / ㎡, and form a consolidation layer on the surface of the sprayed material after drying. Figure 1 shown.

[0141] The plant straw-based dust suppressant forms a thin film after spraying, which has the functions of degradation, adhesion, water retention, film formation and wetting, and is an environmentally friendly green chemical product.

[0142] The actual viscosity of the plant straw-based dust suppressant of this embodiment is 102.27 mPa·s, the anti-evaporation rate is 27.33%, and the surface tension is 25.07 mN / m.

[0143] Example 3

[0144] The raw materials for preparing the plant straw-based dust suppressant in this embodiment are:

[0145] If the ratio is 0.1% hydroxyethyl cellulose (10S), 1.5% wheat straw-based super absorbent resin water retaining agent (prepared in Example 1), and 0.6% cinnamyl glucoside.

[0146] The preparation method of this embodiment is the same as that of embodiment 2.

[0147] The dust suppressant of this embodiment has an actual viscosity of 65.5 mPa·s, an anti-evaporation rate of 25.2%, and a surface tension of 24.8 mN / m.

[0148] Example 4

[0149] The raw materials for preparing the plant straw-based dust suppressant in this embodiment are:

[0150] If the ratio is 0.3% hydroxyethyl cellulose (10S), 2.5% wheat straw-based super absorbent resin water retaining agent (prepared in Example 1), and 0.6% cinnamyl glucoside.

[0151] The preparation method of this embodiment is the same as that of embodiment 2.

[0152] The actual viscosity of the dust suppressant of this embodiment is 2011.2 mPa·s, the anti-evaporation rate is 23.6%, and the surface tension is 24.5 mN / m.

[0153] Experimental Example 1

[0154] Choice of binder:

[0155] Binder is one of the important components of dust suppressant. In this experiment, sodium alginate, hydroxyethyl cellulose (30,000 viscosity), and hydroxyethyl cellulose (100,000 viscosity) were selected for viscosity test at 20°C. If the viscosity is too high, there will be certain limitations on the spraying equipment, which is not conducive to promotion; if the viscosity is too low, the bonding performance of the dust suppressant will not show good performance.

[0156] The determination steps are as follows: prepare 8 groups of sodium alginate, hydroxyethyl cellulose (30,000 viscosity), and hydroxyethyl cellulose (100,000 viscosity) solutions with mass concentrations of 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, and 0.7% respectively, stir them fully at 20°C with a magnetic stirrer until the solute is completely dissolved, then keep the solution temperature at 20°C in a constant temperature water bath, and insert a thermometer to measure the change in solution temperature. The viscosity values ​​of the three binders increase with the increase of mass concentration, among which the viscosity of the hydroxyethyl cellulose (100,000 viscosity) solution changes the fastest with the increase of mass concentration, exceeding 100mpa·s at a mass concentration of 0.4%, so hydroxyethyl cellulose (100,000 viscosity) is preferred as the raw material of the dust suppressant.

[0157] Experimental Example 2

[0158] Choice of surfactant:

[0159] Surfactants, as one of the important components of chemical dust suppressants, have a great influence on the wetting effect of dust. Surfactants of different mass concentrations have an important influence on the wetting performance. Four surfactants, including cinnamyl glucoside, cocamidopropyl betaine, fatty alcohol polyoxyethylene ether, and dodecyl dimethyl ammonium oxide, were selected for surface tension testing.

[0160] The test steps are as follows: 8 groups of solutions with mass concentrations of 0.01%, 0.03%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, and 0.8% are prepared respectively, and stirred evenly with a magnetic stirrer. The four surfactants can quickly reduce the surface tension of the solution. The APG0810 solution reaches 25.2mN / m at a mass concentration of 0.6%, which is lower than the other three surfactants. Therefore, cinnamyl glucoside is selected as the raw material of the dust suppressant.

[0161] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

[0162] Test example:

[0163] 1. Impact of straw-utilizing dust suppressants on soil

[0164] At present, this research group has developed an environmentally friendly composite dust suppressant with hydroxyethyl cellulose (HEC, 3S), propylene glycol, and isotridecyl polyoxyethylene ether as raw materials. As the first generation of dust suppressant products, it already has good bonding properties, water retention properties, etc. This test example conducted pH tests, wind erosion resistance tests, soil testing after spraying, optical microscopy characterization tests, etc. on the straw-utilizing dust suppressant obtained by the response surface method. Finally, the economic benefits of the dust suppressant were analyzed to explore the actual application performance of the straw-utilizing type. As shown in Reference Table 4, the five solutions are numbered H1 to H5. The morphology of the five solutions H1 to H5 after immersion in the soil sample is as follows: Fig.18 shown.

[0165] Table 4 Numbers of dust suppressant solutions and water

[0166]

[0167] contrast Fig.18 From the status of the five soil samples, it can be seen that the soil fixation of the straw-utilizing dust suppressant (H2) is better.

[0168] This test was commissioned to Sichuan Aiyuan Testing Technology Service Co., Ltd., and the sample size was 1kg. The test items included eight elements: total arsenic, total mercury, total lead, total chromium, total cadmium, total copper, total zinc, total nickel, as well as pH and organic matter. The test results are shown in Tables 5 and 6.

[0169] Table 5: pH, organic matter, total arsenic, total mercury, and total copper test results report of soil samples from Sichuan Aiyuan Testing Technology Service Co., Ltd.

[0170]

[0171]

[0172] Table 6 Sichuan Aiyuan Testing Technology Service Co., Ltd. soil sample total zinc, total nickel, total lead, total chromium, total cadmium test results report

[0173]

[0174] The pH values ​​of the five soil samples were between 7.8 and 8.0, which was alkaline. The pH value of the soil at the collection point was tested and the result was 8.7, which was alkaline. The inspection results showed that the pH value of the soil sample was also alkaline, and the plants in the field grew well. Figure 5. Soil organic matter is one of the key factors that determine soil fertility. It plays a vital role in maintaining the balance of the ecosystem, increasing crop yields, and reducing the use of chemical fertilizers. The results of the organic matter test showed that the organic matter content of the soil samples was as follows: soil treated with H1 > soil treated with H2 > soil treated with H4 > soil treated with H3 > soil treated with H5, which indicates that the performance of the straw-utilizing dust suppressant (H2) in promoting soil fertility is lower than that of H1, but higher than that of H3, H4, and H5. The organic matter content of the soil treated with H3, the soil treated with H4, and the soil treated with H5 is almost the same, so H3 and H4 have almost no soil fertility promotion performance, and H2 has a promoting effect on enhancing soil fertility.

[0175] In the detection of eight major elements in the soil, the six indicators of total copper, total zinc, total nickel, total lead, total chromium and total cadmium were all the lowest and met the requirements, indicating that straw-utilizing dust suppressant (H2) is more environmentally friendly and has no harm to the human body and the ecological environment.

[0176] Reference for pH value detection of soil at the collection point Fig.19 shown.

[0177] 2. Optical microscope characterization test of straw-utilizing dust suppressant

[0178] In order to compare the water retention performance of dust suppressant solution sprayed on the soil, three drops of straw-utilized dust suppressant solution (plant straw-based dust suppressant solution), purchased dust suppressant solution, and water were respectively dripped onto a glass slide containing a small amount of dust, and the dust samples were observed after 0min, 1min, and 10min. The water retention performance of the solution was determined by the evaporation rate of the solution. The morphology of the dust samples after 0min, 1min, and 10min of spraying straw-utilized dust suppressant, purchased dust suppressant, and water is shown in the figure. Figure 20 to Figure 22 shown.

[0179] Depend on Fig. 20 , 21 The test results show that when the straw-utilizing dust suppressant solution is dripped, the liquid appears as a dark gray part, and the solution immediately wets the dust sample. After 1 minute, the liquid begins to evaporate and presents a light-colored part. After 10 minutes, the dust sample dripped with the straw-utilizing dust suppressant solution has the smallest light gray part. The dust sample dripped with water has the largest light gray part, indicating that the water evaporates the fastest. It can be seen that the straw-utilizing dust suppressant solution has good water retention performance.

[0180] After the dust suppressant solution evaporated for a period of time, the soil sample sprayed with the straw-utilizing dust suppressant showed filamentous substances, while the soil sample sprayed with water had no obvious filamentous substances. Fig. 22 , 23. Analysis shows that the reason may be that the molecular structure of the surfactant in the dust suppressant solution contains both hydrophilic and hydrophobic groups. The surfactant can significantly reduce the surface tension in the aqueous solution. The hydrophilic groups in the surfactant are tightly connected to the minerals or organic matter in the soil, while the hydrophobic groups are facing the outside of the soil particles. This adsorption effect not only enhances the mutual attraction between soil particles, but also promotes the stability of the soil structure, making the originally loose soil more compact. Therefore, the straw-utilizing dust suppressant can fix the soil particles and form small plates to achieve the dust reduction effect.

[0181] After waiting for 3 hours, the edge of the sample was observed again under an optical microscope. The soil particle morphology after spraying the straw-utilizing dust suppressant and water for 3 hours is as follows Fig.24 , 25 shown.

[0182] The test results are as follows Fig.24 , 25 As shown. The optical microscope test showed that after the dust was treated with the straw-utilizing dust suppressant solution and water for 3 hours, the soil particles had a "agglomeration" phenomenon, indicating that the straw-utilizing dust suppressant solution has cohesive properties and can bind the soil particles together, so that the fine dust particles can be aggregated into larger particles; while the dust particles sprayed with water are relatively loose, and there is little adhesion between the dust particles. The test shows that the straw-utilizing dust suppressant has good cohesive properties, which can bind the particles in the soil together, and can also combine the fine particles in the air into large particles and fall to the ground.

[0183] 3. Eco-friendliness of straw-utilizing dust suppressants

[0184] (1) The straw-utilizing dust suppressant is non-toxic and harmless, and is an eco-friendly solution. However, considering that it may affect the germination and normal growth of plant seeds during on-site spraying, a planting comparison test was designed to determine the effect of the dust suppressant on plant growth. Cabbage seeds suitable for four-season growth were used as the test objects, and the first-generation dust suppressant products, straw-utilizing dust suppressant products, two types of dust suppressants purchased on the market, and water were used as the test objects for a total of 5 groups of tests.

[0185] Spray the five solutions H1, H2, H3, H4 and H5 into five flower pots respectively. Fig.26. In the second pot, after spraying H2, there was a more obvious "film" on the surface. This is because the main raw material of the dust suppressant, the wheat straw-based super absorbent resin water retainer, formed a "micro reservoir" in the soil, which has the effect of retaining and absorbing water; and hydroxyethyl cellulose (HEC, 10S) is sticky and can connect soil particles in series, which plays a role in enhancing soil adhesion and improving soil stability; cinnamyl glucoside (APG0810) can reduce the surface tension of water, thereby improving the wetting properties of the dust suppressant solution. Therefore, the soil surface sprayed with H2 has different phenomena from the soil surface sprayed with H1, H3, H4, and H5. Then evenly spread the cabbage seeds in the flowerpot, cover them lightly with soil, and wait for germination.

[0186] The germination of five pots of Chinese cabbage seedlings is shown in Table 7. The growth of five pots of Chinese cabbage seedlings 96 hours after planting is shown in Table 7. Fig. 27 shown.

[0187] Table 7 Germination of five pots of Chinese cabbage seedlings

[0188]

[0189]

[0190] As can be seen from Table 7, the germination rates of cabbage seeds in pots treated with H1, H2, H3, and H4 solutions were 95%, 100%, 95%, and 95% after 96 hours, and the germination rate of cabbage seeds in pots treated with H5 was 100%, which was the same as the germination rate of spraying H2, and was higher than the germination rate of 95% spraying H1, H3, and H4. This shows that the straw-utilizing dust suppressant (H2) does not affect the growth and germination of plants.

[0191] (2) Growth overview of cabbage seedlings

[0192] 72 hours after planting the cabbage, the growth height of the cabbage seedlings was observed and measured, and the average value was taken as the growth height of each pot of seedlings for comparison. The results are as follows Fig.28 As shown. According to the test results, the cabbage seedlings in the pots sprayed with H5 before 96 hours grew fastest, with an average growth height of 3.33 cm at 96 hours, and the cabbage seedlings in the pots sprayed with H2 grew to an average height of 3.29 cm at 96 hours. The growth rate of cabbage seedlings in the pots sprayed with H2 after 96 hours exceeded that of the cabbage seedlings in the pots sprayed with H5, but the amplitude was small. Analysis shows that the reason may be that the water in the pots sprayed with H5 evaporates faster than that in H2, resulting in insufficient water in the soil of the pots sprayed with H5 in the later period, which further illustrates the advantage of straw-utilizing dust suppressant (H2) in water retention performance.

[0193] 4. Wind erosion resistance test of straw-utilizing dust suppressant

[0194] (1) Determination of spraying amount

[0195] Four 500g soil samples were spread flat on four 40cm×40cm square glass plates respectively, and the soil samples were evenly sprayed on the surface of the glass plates at spraying rates of 1.0L / ㎡ (0.16L), 1.5L / ㎡ (0.24L), 2.0L / ㎡ (0.32L), and 2.5L / ㎡ (0.40L). After drying, the weight was weighed and recorded as N. Subsequently, a Keyue brand hair dryer was used to blow the soil samples for 100 minutes. The mass of the soil samples was recorded every 20 minutes and recorded as n. The mass loss rate of the soil samples after each blowing was calculated by formula 4-1 and recorded as M. The corresponding relationship between wind speed and wind force level is shown in Table 8. The comparison diagram of spraying H2 soil samples before and after blowing is shown in the figure below. Figure 29 to Figure 32 As shown. H2 mass loss rate of soil samples under different spraying rates Fig.33 shown.

[0196]

[0197] Where: M-mass loss rate (%);

[0198] N-weight of soil sample after drying before wind erosion (g);

[0199] n-weight of soil sample after wind erosion (g).

[0200] Table 8 Correspondence between wind speed and wind force level

[0201] instrument Gear Distance measurement (m) Wind speed (m / s) Wind level Blower / 0.5 14.2 7

[0202] Depend on Figure 29-Figure 33 The results show that the wind erosion process can be divided into three stages: the initial water evaporation stage, the mid-term test solution retention stage, and the late soil sample blowing away stage. The early water evaporation is difficult to control, the mid-term dust suppressant plays a consolidation role, making it difficult for soil particles to be lifted up, and the late dust suppressant has a poor consolidation effect, causing the soil particles to be blown away. It can be concluded that dust suppressants can be sprayed again in the late stage of the test solution retention stage to achieve the effect of controlling dust. The specific time point for re-spraying can be adjusted appropriately according to actual conditions.

[0203] The soil sample sprayed with 2.0L / ㎡ (0.32L) had the least mass loss after 100 minutes of wind erosion at level 7, with a wind erosion rate of only 7.50%. The large particles of soil at the edge of the four groups of soil samples after spraying H2 and before erosion were easily blown away. The reason for this is that the soil particles at the edge of the soil samples have more opportunities to contact the air, and the water evaporates faster than the soil samples in the middle part under the blessing of strong wind, resulting in dry and loose soil. The middle part is protected by the surrounding soil, and the water evaporates slowly, so the soil structure is more compact and stable.

[0204] Secondly, there is a lot of gel accumulation on the upper surface of the right edge of the soil sample with a spraying amount of 2.5L / ㎡. This is because the gel-like substance formed by the wheat straw-based resin water retaining agent in H2 has the effect of absorbing and retaining water, but excessive spraying will cause gel accumulation, which will not achieve the desired wind resistance effect. Therefore, the spraying amount of dust suppressant is 2.0L / ㎡.

[0205] (2) Comparison with other dust suppressants

[0206] like Fig.34 As shown in the figure, the horizontal comparison test of different solutions shows that the mass loss rates of spraying H2, H3, H4, and H5 after 100 minutes of blowing are 7.50%, 12.84%, 10.80%, and 13.77%, respectively. The mass loss rate of the soil sample sprayed with the straw-based dust suppressant (H2) is significantly lower than that of the soil sample sprayed with H3, H4, and H5, and the anti-wind erosion performance is the best. From the pictures after blowing, it can be seen that after 100 minutes of blowing, the soil samples sprayed with H3, H4, and H5 have fewer large particles of soil on the three glass plates, indicating that the straw-based dust suppressant (H2) has good anti-wind erosion performance.

Claims

1. Super absorbent resin water retaining agent, characterized by: The method firstly adopts plant straw as raw material to prepare carboxymethyl straw cellulose powder, and then adopts the carboxymethyl straw cellulose powder as raw material to prepare the product through aqueous solution polymerization method.

2. A method for preparing the super absorbent water-retaining agent according to claim 1, characterized in that: The following steps are involved: S1. Wash, dry, cut and then crush and sieve the straw to obtain a plant straw powder sample; S2, mixing the plant straw powder sample with deionized water to obtain a mixed solution; S3, adding alkaline solution to the mixed solution, reacting in a water bath at 30-40°C, then heating to 70-80°C and adding sodium chloroacetate to react for 1-2 hours; S4, filtering, washing and drying the solution obtained by the reaction in step S3 to obtain carboxymethyl straw cellulose powder; S5. Add carboxymethyl straw cellulose powder, acrylic acid-sodium hydroxide mixed solution, initiator, crosslinking agent and deionized water in a three-necked flask in sequence, filter three times with nitrogen, stir and react in a water bath at 65-75°C to form a gel, then heat to 90-98°C and keep warm for 0.5-1h; S6, drying, crushing and sieving the gel obtained in step S5 to obtain a super absorbent resin water retaining agent sample.

3. The preparation method according to claim 2, characterized in that: In S2, 20 to 30 g of plant straw powder sample is mixed with 200 to 300 ml of deionized water to obtain a mixed solution; In S3, 35-45 ml of 20% sodium hydroxide by mass is added to the mixed solution, reacted in a water bath at 30-40° C., then the temperature is raised to 70-80° C. and 15-40 g of sodium chloroacetate is added to react for 1-2 hours; In S5, 10-20 g of carboxymethyl straw cellulose powder, 70-80 ml of acrylic acid-sodium hydroxide mixed solution, 1.5-2 g of initiator, 0.5-0.7 g of cross-linking agent and 100-150 ml of deionized water are added in sequence to a three-necked flask. After nitrogen is passed through and filtered three times, the mixture is placed in a 65-75° C. water bath and stirred to allow a polymerization reaction to occur. The temperature in the flask rises rapidly to form a gel, which is then raised to 90-98° C. and kept warm for 0.5-1 h.

4. The preparation method according to claim 3, characterized in that: In S2, 30 g of plant straw powder sample was mixed with 300 ml of deionized water to obtain a mixed solution; In S3, 40 ml of 20% sodium hydroxide was added to the mixed solution, and the mixture was reacted in a 35°C water bath for 1 hour, and then the temperature was raised to 75°C and 30 g of sodium chloroacetate was added to react for 1.5 hours; In S5, 15 g of carboxymethyl straw cellulose powder, 75 ml of acrylic acid-sodium hydroxide mixed solution, 1.8 g of initiator, 0.6 g of cross-linking agent and 127.5 ml of deionized water are added to a three-necked flask in sequence. After nitrogen is passed through and filtered three times, the mixture is placed in a 70°C water bath and stirred. A polymerization reaction occurs, and the temperature in the flask rises rapidly to form a gel, which is then raised to 95°C and kept warm for 0.5 to 1 h.

5. The preparation method according to claim 2, characterized in that: The straw includes, but is not limited to, one or more of wheat straw, melon straw, chili straw, bean straw, rice straw, eggplant straw, corn straw, licorice straw, and bamboo poles.

6. The preparation method according to claim 2, characterized in that: In the step S5, the initiator is potassium persulfate; and / or The crosslinking agent is N,N'-methylenebisacrylamide.

7. Plant straw-based dust suppressant, characterized in that: Prepared from the following components: 0.1% to 0.3% binder, 1% to 4% water retaining agent, 0.1% to 0.8% surfactant, and the balance is deionized water; Wherein, the water-retaining agent is the highly water-absorbent resin water-retaining agent described in claim 1, or the highly water-absorbent resin water-retaining agent prepared by the preparation method described in any one of claims 2 to 5.

8. The plant straw-based dust suppressant according to claim 7, characterized in that: The pH value of the plant straw-based dust suppressant is 6.5-7.

9. The plant straw-based dust suppressant according to claim 7, characterized in that: The surfactant is cinnamyl glucoside.

10. The plant straw-based dust suppressant according to claim 7, characterized in that: The binder is hydroxyethyl cellulose, and the viscosity of the hydroxyethyl cellulose is 100,000.

Citation Information

Cited By

  • Wheat straw-based agriculture and forestry water-retaining agent and preparation method thereof

    CN121226571A